2004
DOI: 10.1186/bcr784
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between intratumoral expression of genes coding for xenobiotic-metabolizing enzymes and benefit from adjuvant tamoxifen in estrogen receptor alpha-positive postmenopausal breast carcinoma

Abstract: IntroductionBreast cancer growth is regulated by estrogen, which acts by binding to its estrogen receptor alpha (ERα). The presence of ERα in breast tumors is used as a biological marker to identify patients who may respond to endocrine agents such as tamoxifen. However, one-half of the patients with ERα-positive tumors fail to respond favorably to antiestrogen treatment [1,2]. ABCC1 = ATP binding cassette C1 isoform; AUC = area under the curve; CYP2A6 = cytochrome P450 2A6 isoform; CYP2B6 = cytochrome P450 2B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
85
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 28 publications
5
85
0
2
Order By: Relevance
“…In addition, to CYP2B6 and CA12 that are already known to be ERa-related in breast cancer (Gruvberger et al 2001, Bieche et al 2004b, we identified a third gene (IL6ST) that perfectly predicted ERa status in our breast tumor series (AUC-ROC, 1.000). IL6ST encodes gp130, the subunit shared by the different receptors of IL-6 family cytokines, including interleukin-6, interleukin-11, leukemia inhibitory factor, oncostatin M, ciliary neurotrophic factor, and cardiotrophin-1 (Kishimoto et al 1994).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…In addition, to CYP2B6 and CA12 that are already known to be ERa-related in breast cancer (Gruvberger et al 2001, Bieche et al 2004b, we identified a third gene (IL6ST) that perfectly predicted ERa status in our breast tumor series (AUC-ROC, 1.000). IL6ST encodes gp130, the subunit shared by the different receptors of IL-6 family cytokines, including interleukin-6, interleukin-11, leukemia inhibitory factor, oncostatin M, ciliary neurotrophic factor, and cardiotrophin-1 (Kishimoto et al 1994).…”
Section: Discussionmentioning
confidence: 78%
“…The only gene showing significantly different expression (PZ0.024) between patients, who relapsed (nZ12) and those, who did not relapse (nZ12) was NAT1. It is noteworthy that, in a previous study of 125 ERa-positive postmenopausal breast cancer patients, we identified NAT1 and CGA (also identified in the present study) as independent predictors of the response to tamoxifen (Bieche et al 2001b(Bieche et al , 2004b.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Several studies have shown higher mRNA and protein expression of NAT1 in ER-positive breast cancer compared with the expression in ER-negative disease (Perou et al 2000, Adam et al 2003, Tozlu et al 2006, Wakefield et al 2008. Moreover, it was reported that high expression of NAT1 was correlated with better outcome in ER-positive breast cancer (Bieche et al 2004, Dolled-Filhart et al 2006. Our results demonstrated that NAT1 mRNA expression was much higher in ER high Ki67 low tumors than in ER Gene expressions of miR-1290 putative targets in T47D and MCF-7 cells transfected with miR-1290.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the clearance of nicotine and cotinine was significantly higher during pregnancy (Dempsey et al, 2002). In addition to these findings, a recent in vitro study demonstrated that the expression level of CYP2A6 mRNA was significantly higher in estrogen receptor ␣ (ER␣; NR3A1)-positive breast tumors than in ER␣-negative breast tumors (Bièche et al, 2004). This background prompted us to investigate the roles of estrogen in regulating CYP2A6.…”
mentioning
confidence: 97%